Text mining national commitments towards agrobiodiversity conservation and use - Juventia, Stella D.; Jones, Sarah K.; Laporte, Marie-Angélique; Remans, Roseline; Villani, Chiara; Estrada-Carmona, Natalia (MDPI, 2020)
Capturing countries’ commitments for measuring and monitoring progress towards certain goals, including the Sustainable Development Goals (SDGs), remains underexplored. The Agrobiodiversity Index bridges this gap by using text mining techniques to quantify countries’ commitments towards safeguarding and using agrobiodiversity for healthy diets, sustainable agriculture, and effective genetic resource management. The Index extracts potentially relevant sections of official documents, followed by manual sifting and scoring to identify agrobiodiversity-related commitments and assign scores. Our aim is to present the text mining methodology used in the Agrobiodiversity Index and the calculated commitments scores for nine countries while identifying methodological improvements to strengthen it. Our results reveal that levels of commitment towards using and protecting agrobiodiversity vary between countries, with most showing the strongest commitments to enhancing agrobiodiversity for genetic resource management followed by healthy diets. No commitments were found in any country related to some specific themes including varietal diversity, seed diversity, and functional diversity. The revised text mining methodology can be used for benchmarking, learning, and improving policies to enable conservation and sustainable use of agrobiodiversity. This low-cost, rapid, remotely applicable approach to capture and analyse policy commitments can be readily applied for tracking progress towards meeting other sustainability objectives.